1985
DOI: 10.1007/bf00125475
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on mode III fatigue thresholds

Abstract: The purpose of this note is to report some preliminary results from a study of near-threshold fatigue crack growth in a rail steel under mode III loading and, on the basis of these results, to make some general observations concerning the nature of mode III fatigue threshold. Table 1 contains the chemical composition and mechanical properties of the standard carbon rail steel used in this investigation.Edge-notched bar specimens having square cross-section were machined from the head of a heavy haul rail.Mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1989
1989
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Pook [9] noted that different thresholds could be found for microscopic crack growth, crack arrest and specimen failure. Hellier et al [12] similarly defined the mode I11 threshold as the boundary between no crack growth and facetted crack growth. Evaluation of branch crack stress intensity factors is difficult.…”
Section: Fatigue Thresholds Under Mixed Mode (I + 111) Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pook [9] noted that different thresholds could be found for microscopic crack growth, crack arrest and specimen failure. Hellier et al [12] similarly defined the mode I11 threshold as the boundary between no crack growth and facetted crack growth. Evaluation of branch crack stress intensity factors is difficult.…”
Section: Fatigue Thresholds Under Mixed Mode (I + 111) Loadingmentioning
confidence: 99%
“…Substituting equations (8) and (10) into equation(12) and considering the cyclic values of the stress intensity factor range, thenA No facets Facetsz] C O S~ +2 25. [ -i:::] sin 4 = 1…”
mentioning
confidence: 99%
“…Fractographic studies of mixed mode (I + 111) fatigue specimens have shown that fine mode I facets are formed close to the slit tip and in some cases [5,7] co-planar crack growth at the crack tip occurs, similar to the shear cracks observed in mode 111 [9,10] and in mixed mode (If 11) fatigue [I 11.…”
Section: Fatigue Thresholds Under Mixed Mode (I + 111) Loadingmentioning
confidence: 99%
“…Unlike mode I fatigue testing there is no generally accepted definition of the fatigue threshold under mode I11 or mixed mode conditions. Thresholds have been variously defined by the lowest stress intensity factor range at which mode I11 flat crack growth occurred [12], or the lowest stress intensity factor range for the formation of mode I branch cracks or facets [2,7,10,13,14]. Different thresholds can be found for microscopic crack growth, crack arrest and specimen failure.…”
Section: Fatigue Thresholds Under Mixed Mode (I + 111) Loadingmentioning
confidence: 99%
“…As for the threshold condition for the branch (mode I) crack formation, Pook [5] proposed the maximum principal criterion, while Yates and Miller [6] proposed the critical crack-tip opening displacement (mode I) criterion. Yates and Miller [6], and Hellier et al [7] observed small microscopic flat fracture surfaces very near to the initial notches. The condition for the formation of this flat fracture is not yet known.…”
mentioning
confidence: 95%